An integrative approach for the transplantation of high-risk sensitized patients - Morath, Christian; Beimler, Jörg; Opelz, Gerhard; Ovens, Jörg; Scherer, Sabine; Schmidt, Jan; Schmied, Bruno; Groß-Weissmann, Marie-Luise; Schwenger, Vedat; Zeier, Martin; Süsal, Caner (Transplantation, 2010)
Background. - Sensitized patients have a lower chance of receiving a crossmatch-negative kidney and, if transplanted, are at risk of antibody-mediated allograft rejection. - Methods. - For safe and timely transplantation of sensitized patients at our center, we developed an integrative algorithm that includes identification of high-risk patients, good human leukocyte antigen match, inclusion in the Eurotransplant Acceptable Mismatch Program when applicable, apheresis, anti-CD20 therapy, posttransplant antibody monitoring, and protocol biopsies. Thirty-four high-risk recipients of a deceased donor kidney (DDK: n=28) or living donor kidney (LDK: n=6) were transplanted using this algorithm. - Results. - One-year graft survival, death-censored graft survival, and patient survival rates in DDK recipients were 92.4%, 96.4%, and 95.8%, respectively. No graft loss or patient death was observed in the six LDK patients. Median serum creatinine at 1 year in DDK and LDK recipients was 1.2 and 1.4 mg/dL, respectively. Eleven DDK and three LDK patients experienced at least one biopsy-proven acute rejection episode, mostly showing borderline changes. Antibody-mediated rejection without graft loss was diagnosed in two DDK and one LDK patients. Delayed graft function was observed in 13 DDK and 1 LDK patients. Infectious complications were infrequent. - Conclusions. - We describe an algorithm for the categorization and treatment of presensitized high-risk patients. This protocol provides effective prevention of antibody-mediated rejection and is associated with a low rate of side effects and good graft outcome.